Single-cell profiling unveils key regulators of skeletal stem cells in chicken and human embryonic limb development - Ruohan Zhao; Zonghui Jian; Fangxiao Yang; Kun Wang; Lixian Liu; Zhiqiang Xu; Junjing Jia; Tengfei Dou; Xiaoming He (PLoS ONE, 2026)
Skeletal stem cells (SSCs) are well characterized in humans and mice, providing valuable insights into bone development and regeneration. However, their identification in poultry, particularly in chicken embryos, remains limited. In the present study, we used single-cell transcriptomic profiling to compare the cellular composition and functionality of human and chicken embryonic limb buds. Our cross-species analysis revealed high conservation of key cell types, such as mesenchymal and osteochondral progenitors, alongside notable heterogeneity in individual gene expression profiles. We identified the conserved and species-specific gene expression patterns in chicken SSCs. Differential expression analysis combined with Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and protein-protein interaction (PPI) networks suggested that COL5A2 , COL1A2 , PRRX1 , and TGFβ2 may serve as key regulators of chicken SSCs. Immunofluorescence assays confirmed the predominant localization of these genes in the periosteal region, with minor expression in the primary ossification centers. This study enhances our understanding of cellular diversity in chicken embryonic limb buds and highlights conserved and divergent mechanisms across species, offering insights for future SSC research and animal model selection in skeletal biology.